Strategy Development: Most Signficant Change (MSC) Toolkit (ODI, 2009)
The Most Significant Change (MSC) technique is a form of participatory monitoring and evaluation. It is participatory because many project stakeholders are involved both in deciding the sorts of change to be recorded and in analysing the data. It is a form of monitoring because it occurs throughout the programme cycle and provides information to help people manage it. MSC contributes to evaluation because it provides data on impact and outcomes which can be used to help assess the performance of the programme as a whole. Essentially, the process involves the collection of significant change (SC) stories emanating from the field level, and the systematic selection of the most important of these by panels of designated stakeholders or staff. The designated staff and stakeholders are initially involved by ‘searching’ for project impact. Once changes have been captured, various people sit down together, read the stories aloud and have regular and often in-depth discussions about the value of the reported changes. When the technique is successfully implemented, whole teams of people begin to focus their attention on programme impact. MSC has had several names since it was conceived, each emphasising a different aspect. Examples are: ‘Monitoring-without-indicators’ – MSC does not make use of predefined indicators, especially ones which have to be counted and measured; or the ‘story approach’ – the answers to the central question about change are often in the form of stories of who did what, when and why, and the reasons the